Design and simulation analysis of a dual-source magnetic loop structure for mining steel wire rope - ZHOU Ping; WANG Shihao; ZHOU Gongbo; ZHAO Tianchi; LI Xuanhan; YAN Xiaodong (Gong-kuang zidonghua)
Currently, the electromagnetic detection methods for mining steel wire ropes have limitations: the main flux detection method has low accuracy in detecting local damage, while magnetic leakage-based detection methods have limited quantitative accuracy in local damage assessment. A dual-source magnetic detection method was proposed to simultaneously detect both the main flux and magnetic leakage in mining steel wire ropes, leveraging the complementary strengths of these two methods in local damage detection. Two excitation loop designs were proposed: a double-source ring-shaped tubular excitation loop and an independent separation excitation loop. Finite element simulation was used to verify the feasibility of the two schemes, and the independent separation loop was chosen as the basic structure of the magnetic circuit. The effects of various armature parameters, such as size and magnet properties, on the magnetization performance were studied, as well as the influence of the magnetic bridge structure parameters on the magnetic field distribution. The results indicated that:① The magnetization amplitude was positively correlated with the number of loops and negatively correlated with the armature length, while the height had almost no effect on the magnetization performance; ② The magnetization amplitude was positively correlated with the material grade, length, and thickness, and negatively correlated with the lift-off distance; ③ The magnetization amplitude was positively correlated with thickness, negatively correlated with air gap size, while lift-off distance had little effect on the magnetization performance; ④ The air gap of the magnetic bridge significantly influenced the magnetic flux density distribution within the bridge circuit.